2006
DOI: 10.1007/s10826-006-9042-0
|View full text |Cite
|
Sign up to set email alerts
|

From Intent to Enrollment, Attendance, and Participation in Preventive Parenting Groups

Abstract: Applying the Theory of Planned Behavior (TPB) to the process of engagement in preventive parenting groups, we tested the ability of family and child measures to predict intent to enroll, enrollment, attendance, and quality of participation in PACE (Parenting Our Children to Excellence). PACE is a prevention trial testing the efficacy of a structured program to promote effective parenting and reduce risk of adverse child outcomes. Mothers of preschoolers (N = 451) from diverse ethnic and socioeconomic backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
120
0
17

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 40 publications
20
120
0
17
Order By: Relevance
“…Thus, studies generally find that only around 15-30% of the target population enroll for program participation, and that often only about 50% of those who have enrolled effectively fully comply with the intervention (Dumas et al 2007;Dumka et al 1997;Haggerty et al 2002;Heinrichs et al 2005;Morawska and Sanders 2006;Spoth et al 2000). Such low exposure rates mean that treatment effects become highly diluted amongst the intended target group, and that an intention-to treat analysis of a randomized experiment yields results that are of limited value.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, studies generally find that only around 15-30% of the target population enroll for program participation, and that often only about 50% of those who have enrolled effectively fully comply with the intervention (Dumas et al 2007;Dumka et al 1997;Haggerty et al 2002;Heinrichs et al 2005;Morawska and Sanders 2006;Spoth et al 2000). Such low exposure rates mean that treatment effects become highly diluted amongst the intended target group, and that an intention-to treat analysis of a randomized experiment yields results that are of limited value.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in a study of 1,121 families' involvement in a parenting skills intervention, Spoth et al (1997) found that inclination to participate (i.e., intention) in the intervention predicted subsequent enrollment. Similarly, in an example of 451 mothers of preschoolers, Dumas et al (2007) found that intent to enroll was the best predictor of enrollment in a program promoting effective parenting. A number of studies suggest the 5 importance of socio-demographic factors in decisions to participate in parenting education (e.g., Perrino et al, 2001;.…”
mentioning
confidence: 97%
“…The theory of planned behavior model (TPB) (Ajzen 1991) has been applied widely to predict engagement in health behaviors (Armitage and Conner 2001) and services (Dumas et al 2007), suggesting its relevance as a model for examining individuals' engagement in mental health services. According to the TPB, behaviors are largely determined by the individual's intention to perform a behavior, where intentions are a function of three domains: (a) the individual's attitude toward the behavior, (b) the subjective norms associated with the performance of the behavior, and (c) the individual's perception of efficacy in performing the behavior (Ajzen 1991).…”
Section: Theory Of Planned Behavior-internal Processes Of Engagementmentioning
confidence: 99%